Patient Participation and the Use of Ehealth Tools for Pharmacoviligance - Berrewaerts, Joëlle; Delbecque, Laure; Orban, Pierre; Desseilles, Martin (Frontiers in Pharmacology, 2016)
In recent years, pharmacovigilance has undergone some major changes. First, the patient’s active role in identifying and describing adverse drug reactions (ADRs) has gained recognition. Second, pharmacovigilance has increasingly incorporated information and communications technology (ICT). Patients can now upload their own reports of ADRs online. Data on intensive medication monitoring are now collected via the Internet and smartphones. Worldwide collection of AEs using smart phones might become the leading technique in Low and Middle Income Countries where broad mobile phone service can be managed cheaper than Internet communication. At the same time, researchers are exploring the potential for data sharing via online forums and Internet search engines. In particular we synthetize the Pros and cons of the various methods for gathering pharmacovigilance data (i.e. Web-based spontaneous reporting of adverse drug reactions; Intensive drug monitoring studies; Analysis of online forum postings; Use of mobile phone systems to monitor drug effects). This article describes these advances and highlights their respective contributions.